Inequality in individual mortality and economic conditions earlier in life - Gerard van den Berg; Maarten Lindeboom; Marta Lopéz (Institute for Labour Market Policy Evaluation (IFAU), 2007)
We analyze the effect of being born in a recession on the mortality rate later in life in conjunction with social class. We use individual data records from Dutch registers of birth, marriage, and death certificates, covering the period 1815-2000, and we merge these with historical data on macro-economic outcomes and health indicators. We estimate duration models and inequality measures. The results indicate that being born in a recession increases the mortality rate later in life for most of the population. Lower social classes suffer disproportionally from being born in recessions. This exacerbates mortality inequality. This is not affected by social mobility: upward mobility does not vary much with the business cycle at birth, for each social class.
Keywords: C41; E32; I12; J14; N13; N33; 330; Death; longevity; recession; life expectancy; lifetimes; social inequality; social class; health; Sterblichkeit; Lebensverlauf; Soziale Lage; Soziale Ungleichheit; Niederlande